Synthesis And Characterization Of Titanium Dioxide Particles By Direct Heating Technique For Photodegradation Of Methylene Blue Solution - Ng, Guan Sheng (Universiti Sains Malaysia, 2022)
Dyes are extensively used in textile industry and it will release large amount of dye-containing wastewater which is hazardous to human and environment. Advanced oxidation process (AOPs) based on heterogeneous TiO2 photocatalyst is one such technology that has proven successful for effluent treatment. The aim of this research work is to synthesize TiO2 particles on Kanthal wire by using Direct Heating technique with different heating duration and heating power. TiO2 particles that grown on Kanthal wire and its by product was measured in terms of its structural, optical and photocatalytic performances. The precursor solution was prepared by mixing 5 ml of titanium tetraisopropoxide (TTIP) with 15 ml isopropanol. A 250 ml solution of distilled water mixed with hydrochloric acid solution (HCl) to reach pH 1. Then, 2 drops of hydrogen peroxide (H2O2) were added to the mixture solution to promote the formation of TiO2. The Kanthal coil was immersed into the mixture solution. The AC regulator was switched on for 60 W and 30 minutes, then the wire coil was rinsed with distilled water, air dried and was characterized by various characterization techniques. The optimum synthesis condition for Direct Heating was heating duration of 15 min and heating power of 60 W. Optimum deposited TiO2 contained mixture of anatase (82.7%) and brookite (17.3%), average particle size of 167.36±15.37 nm, surface coverage of TiO2 particles on Kanthal wire was good, with minimum agglomeration, and the highest photodegradation efficiency (43.7%). TEM shows the presence of aligned nanorods and nanoparticles (with the size of 5.766 ± 1.302 nm), and EDX spectrum further confirms the presence of TiO2 deposited on Kanthal wire. The by-product TiO2 particles has a higher photodegradation efficiency (36.5 %) than the commercial TiO2 particles (16.3 %). Besides, by-product TiO2 particles was used for scavenger test. The major reactive species in the degradation of MB was •OH.